New syllabus mathematics 3 (fifth edition) - Seng, Keng (Oxford University Press Malaysia)
New Syllabus Mathematics (NSM) is a series of textbooks where the inclusion of valuable learning experiences, as well as the integration of real-life applications of learnt concepts serve to engage the hearts and minds of students sitting for the GCE O-level examination in Mathematics. The series covers the new Cambridge O Level Mathematics ( Syllabus D) 4024/4029 for examinations in 2018, 2019, and 2020. The newly formatted questions which require application of mathematical techniques to solve problems have been inducted.